Development of Flipbook-Based Digital Teaching Media to Increase Student Learning Interest in Science Material - Nurul Aflah; Sujarwo (Global Action and Education for Society, 2026)
In this research and development aims to produce a product in the form of digital teaching media based on Flipbook on the subject of Science and Natural Sciences, the product developed is then tested for its feasibility by experts and gets responses from teachers and students. The design used by researchers to develop digital teaching media based on Flipbook is a design with the ADDIE development model. This research was applied to fourth grade students on the material